MASYARAKAT PULAU RAAS KONTEKS STRUKTURAL-ANTROPOLOGI C. LÉVI-STRAUSS - Anas Ahmadi (Universitas 17 Agustus 1945 Surabaya, 2012)
Abstract. This research is about the structural-antropology of Raas island C. In Levi-Strauss’ structural-antrophology point of view. Levi-Strauss’ structural-antropology include: (1) structural-ecology, (2) structural-economy, (3) structural-sociology, and (4) structural-cosmology. The analysis shows that there is a binary opposition of ocean-land (diadic) based on structural-ecological analysis. In structural-economic analysis, Raas people shows farmer-fisher binary opposition (diadic). Structural-sociologically, Raas people perform triadic opposition: lower, middle, and upper. Cosmologically, Raas people perform triadic opposition: black-liminal-white type of humans. Key Words: People of Raas Island, structural-antrophology C. Lévi-Strauss, structural ecology